PEWARNAAN KAYU SENGON (Paraserianthes falcataria Linn) DARI EKSTRAK LIMBAH KULIT KAYU BAKAU (Rhizophora apiculata Blume) : UJI KETAHANAN WARNA DAN KEAWETAN KAYU - Wardyani, Yuli; Diba, Farah; Nurhaida, . (JURNAL HUTAN LESTARI, 2017)
Sengon (Paraserianthes falcataria Linn) wood is widely used as a particular furniture and craft materials due to many supply and low cost. But Sengon wood has a color that tends to be white and has a low-grade durable IV-V. Mean while the bark of Rhizophora apiculata Blume mangrove was unutilized and made a huge waste, so its need optimal handling. Staining of sengon wood from mangrove bark extract is expected to provide new innovations in increasing the value of environmentally friendly wood decorative and can increase the value of wood sengon timber. Natural dye extract of mangrove bark waste using concentration of 2.5%, 5%, 7%, and 10% dye solution applied on Sengon wood. The results showed that the color endurance at concentrations of 2.5% to 5% was quite good compared to the concentrations of 7.5% and 10%. This is proved by evidence of the value color change before the test with the color of wood after testing using hot and cold water. The highest termite mortality value occurred at a concentration of 10% and the lowest weight loss of the colored test sample was found at a concentration of 10%. At concentration 5% has shown the optimal result in increasing the durability value of Sengon wood which initially with class durable IV-V become class durable II. Dye extract of mangrove bark waste Rhizophora apiculata Blume can be used as dye and increased the durability value of Sengon wood with optimum concentration for the purpose of staining and durability of wood is at concentration 5%.Keywords: C. curvignathus, Concentration, Natural Dye, Sengon, Waste Mangrove Bark